2014
DOI: 10.3892/ol.2014.2771
|View full text |Cite
|
Sign up to set email alerts
|

Shikonin induces apoptosis and inhibits migration of ovarian carcinoma cells by inhibiting the phosphorylation of Src and FAK

Abstract: The present study identified that shikonin, a naphthoquinone extracted from the roots of Lithospermum erythrorhizon, inhibits the migration of ovarian cancer cells and induces their apoptosis by impairing the phosphorylation of two kinases, proto-oncogene tyrosine protein kinase Src (Src) and focal adhesion kinase (FAK). Ovarian carcinoma SKOV-3 cells were treated with various concentrations of shikonin and analyzed for the effects on cell migration, invasion and apoptosis via Transwell assays and flow cytomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
(33 reference statements)
5
8
0
Order By: Relevance
“…The mechanism associated with shikonin-related anticancer activity is poorly understood. A recent study demonstrated that shikonin inhibits the growth of SKOV3 cells, induces their apoptosis, and reduces their migration through inhibiting the phosphorylation of Src and FAK; these results are consistent with those reported in our study [ 28 ]. Another study also demonstrated the application of shikonin-loaded antibody-armed nanoparticles for targeted therapy in ovarian cancer[ 29 ].…”
Section: Discussionsupporting
confidence: 94%
“…The mechanism associated with shikonin-related anticancer activity is poorly understood. A recent study demonstrated that shikonin inhibits the growth of SKOV3 cells, induces their apoptosis, and reduces their migration through inhibiting the phosphorylation of Src and FAK; these results are consistent with those reported in our study [ 28 ]. Another study also demonstrated the application of shikonin-loaded antibody-armed nanoparticles for targeted therapy in ovarian cancer[ 29 ].…”
Section: Discussionsupporting
confidence: 94%
“…2) is an active naphthoquinone, which is derived from the dried root of Lithospermum erythrorhizon, Arnebia euchroma and Arnebia guttata, and it possesses anti-oxidative, anti-inflammatory, and anti-cancer activities [591][592][593][594]. It is effective in treating different kinds of cancers, including breast, prostate, ovarian and thyroid cancers, Ewing sarcoma, and myelomonocytic lymphoma [595][596][597][598][599][600]. Shikonin exerts anti-cancer effects mainly by inducing apoptosis, necroptosis, autophagy, cell cycle arrest, and by inhibiting cell proliferation, growth and metastasis [593,601,602].…”
Section: Shikoninmentioning
confidence: 99%
“…Based on its ability to induce apoptosis in tumor tissue, SK has been widely investigated in cancer treatment [27][28][29][30]. In recent years, the antiapoptotic effects of SK have been gradually discovered in lung injury [31], myocardial ischemic/reperfusion injury [32], osteoarthritis [33], and nervous system diseases [18,20,34].…”
Section: Discussionmentioning
confidence: 99%